Abortion patients' preferences for care and experiences accessing services in Louisiana - Erin Carroll; Kari White (Elsevier, 2020)
Objective: The objective was to compare abortion patients' expectations and preferences for care with their experiences accessing services in Louisiana where there are numerous restrictive abortion laws. Study design: Between June 2018 and January 2019, we conducted in-depth interviews with 35 English-speaking Louisiana residents who were ≥18 years of age and seeking care from the three in-state facilities to explore their perspectives and experiences locating, obtaining and paying for abortion services. We analyzed interview transcripts using a theme-based approach and categorized themes into dimensions of health care access: availability/accessibility, accommodation, acceptability and affordability. Results: Participants were surprised to learn that there were so few facilities providing abortion, which required some of them to drive between 1 and 3 h to the nearest clinic. Many were unable to schedule their visits at a convenient time or obtain care as early in pregnancy as desired because the next available appointment was often a week or more away. Protestor activity and congested waiting rooms did not provide most patients their desired level of privacy, but participants expressed diverse views about other approaches to care that would maintain their confidentiality. To pay for an unplanned health care expense that was not covered by insurance, many participants deferred paying monthly bills and borrowed money, which contributed to financial hardships and additional delays in care. Conclusions: Many Louisiana abortion patients' expectations and preferences for care are not being met across multiple dimensions of health care access assessed in this study, and the state's highly regulated policy environment may limit options for tailoring services to patients' needs. Implications: Abortion patients in Louisiana value accessible, timely, private and affordable services, but a constrained network of providers and medically unnecessary requirements make it difficult for them to obtain patient-centered care. Federal- and state-level policy changes, as well as local initiatives, could ensure abortion patients have access to quality, evidence-based services.